Structural basis for the adaptation and function of chlorophyll f in photosystem I - 宮﨑 直幸; Kato Koji; Shinoda Toshiyuki; Nagao Ryo; Akimoto Seiji; Suzuki Takehiro; Dohmae Naoshi; Chen Min; Allakhverdiev Suleyman I.; Shen Jian-Ren; Akita Fusamichi; Tomo Tatsuya (Nature Communications, 2020)
Chlorophylls (Chl) play pivotal roles in energy capture, transfer and charge separation in photosynthesis. Among Chls functioning in oxygenic photosynthesis, Chl f is the most red-shifted type first found in a cyanobacterium Halomicronema hongdechloris. The location and function of Chl f in photosystems are not clear. Here we analyzed the high-resolution structures of photosystem I (PSI) core from H. hongdechloris grown under white or far-red light by cryo-electron microscopy. The structure showed that, far-red PSI binds 83 Chl a and 7 Chl f, and Chl f are associated at the periphery of PSI but not in the electron transfer chain. The appearance of Chl f is well correlated with the expression of PSI genes induced under far-red light. These results indicate that Chl f functions to harvest the far-red light and enhance uphill energy transfer, and changes in the gene sequences are essential for the binding of Chl f.